2018
DOI: 10.3389/fneur.2018.01087
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compound Targeting Protease Receptor 1 Activators for the Treatment of Glioblastoma

Abstract: Data from human biopsies, in-vitro and in-vivo models, strongly supports the role of thrombin, and its protease-activated receptor (PAR1) in the pathology and progression of glioblastoma (GBM), a high-grade glial tumor. Activation of PAR1 by thrombin stimulates vasogenic edema, tumor adhesion and tumor growth. We here present a novel six amino acid chloromethyl-ketone compound (SIXAC) which specifically inhibits PAR1 proteolytic activation and counteracts the over-activation of PAR1 by tumor generated thrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The involvement of PAR-1 was further con rmed by use of a speci c inhibitor SCH-79797. It was observed that use of speci c inhibitor SCH-79797 signi cantly reduced the TFLLR induced increase in the migration and invasion of D-54 MG. Our results are in line with many previous studies both in rodents and human tissues that have reported active involvement of PAR-1 receptors in the progression of Glioblastoma multiforme [44]. These results along with ours suggest an association between PAR-1 expression and glioma migration.…”
Section: Discussionsupporting
confidence: 93%
“…The involvement of PAR-1 was further con rmed by use of a speci c inhibitor SCH-79797. It was observed that use of speci c inhibitor SCH-79797 signi cantly reduced the TFLLR induced increase in the migration and invasion of D-54 MG. Our results are in line with many previous studies both in rodents and human tissues that have reported active involvement of PAR-1 receptors in the progression of Glioblastoma multiforme [44]. These results along with ours suggest an association between PAR-1 expression and glioma migration.…”
Section: Discussionsupporting
confidence: 93%
“…We chose to modulate this pathway using the specific N-terminal PAR1 sequence recognized by thrombin as a template for the unique PARIN5 molecule, aiming to specifically inhibit PAR1 activation by thrombin. The PARIN5 molecule was previously designed as part of a set of molecules which differ in their backbone length, based on the thrombin recognition site sequence of PAR1, and found to be potent PAR1 inhibitors [ 21 ]. Based on the specificity of the protease-binding site on PAR1 in comparison to PAR3 and PAR4, it is reasonable to attribute the specificity of PARIN5 to PAR1.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction induces resistance to apoptosis and to cytotoxic agents via increased level of Bcl and inhibition of Bim [95]. Recently a specific inhibitor, which prevents activation of PAR1 at thrombin (and thrombin-like protease) cleavage site, resulted in decreased proliferation and improved survival in vivo in glioblastoma [96]. This inhibitor was not designed to block KLK6-mediated activation of PAR1; however, this study highly supports that the KLK6/PAR1 pathway could be a potential target in glioma.…”
Section: Klks In Glioblastoma Progressionmentioning
confidence: 99%